Incidencia de las medidas de salvaguardias arancelarias de marzo del 2015, en los ingresos de los comerciantes de prendas de vestir de origen colombiano, en el sector bahía General Villamil-Manabí de la ciudad de Guayaquil - Bravo Arámbulo, Glenda Noemí (2016)
This study seeks to analyzes how the implementation of measures of safeguards tariff applied by the Ecuadorian government in March 2015, affected certain productive sectors, and in particular the affectation on sales volumes and income, to the Colombian clothing merchants in the sector of the Bahia (GENERAL VILLAMIL- MANABÍ) of the city of Guayaquil, as they saw decrease their business by these tariffs. This activity has become in an important source of income for families of lower middle class, which contributes to the socio-economic development of many cities. The safeguards came into effect on March, 11, 2015 with duration of 15 months and were subsequently authorized by the Andean Community of Nations, so that the country can correct the deficit in the balance of payments and additionally to regain competitiveness against currency devaluation of the neighbor countries of Peru and Colombia………